2021
DOI: 10.52547/jibs.7.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and biology of male, female and larvae of Diaphanes lutescens (Walker) (Coleoptera: Lampyridae: Lampyrinae) in Sri Lanka

Abstract: Diaphanes lutescens was originally described by Walker, 1858, using specimens from Sri Lanka. The systematics and biology of this species has been unexplored since it was first described in the early eighteenth century. This paper provides a detailed description of systematics and biology of the identified male, female and larvae of D. lutescens with their areas of incidence and habitat types in Sri Lanka. Females and larvae were identified when they were associating with males in the same habitat. Remarks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In addition, L. nicollieri has orange pronotum, which distinguish from L. horni by yellowish gold pronotum with median dark mark. Considering the Luciola fireflies in Sri Lanka, Wijekoon et al (2021) reported three species [L. extricans (Walker, 1858), L. horni (Bourgeois, 1905) and L. praeusta (Kiesenwetter, 1874)] out of the recorded 14 Lampyrids from Sri Lanka during 2010-2015 study period. Among them, identity of L. praeusta was confirmed later by authors as Abscondita perplexa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, L. nicollieri has orange pronotum, which distinguish from L. horni by yellowish gold pronotum with median dark mark. Considering the Luciola fireflies in Sri Lanka, Wijekoon et al (2021) reported three species [L. extricans (Walker, 1858), L. horni (Bourgeois, 1905) and L. praeusta (Kiesenwetter, 1874)] out of the recorded 14 Lampyrids from Sri Lanka during 2010-2015 study period. Among them, identity of L. praeusta was confirmed later by authors as Abscondita perplexa.…”
Section: Discussionmentioning
confidence: 99%
“…nov. , Sclerotia substriata (Gorham, 1880) (Ballantyne et al, 2016), Asymmetricata humeralis (Walker) comb. nov. (Ballantyne & Lambkin, 2009), Luciola extricans Walker and L. horni Bourgeois were recorded in recent studies (2010-2021) of Sri Lanka (Wijekoon et al, 2021). Wijekoon et al (2012) tentatively identified a specimen similar to the L. nicollieri, whereas, it was not confirmed because they collected and identified the specimens at night in the field and then released them, so that was impossible to confirm the identifications.…”
Section: Introductionmentioning
confidence: 99%